2021
DOI: 10.1007/s00406-021-01298-0
|View full text |Cite
|
Sign up to set email alerts
|

A neuropsychological study on Leonhard’s nosological system

Abstract: Phenotype validation of endogenous psychosis is a problem that remains to be solved. This study investigated the neuropsychological performance of endogenous psychosis subtypes according to Wernicke-Kleist-Leonhard's classification system (WKL). The participants included consecutive admissions of patients with schizophrenia spectrum disorder or mood disorder with psychotic symptoms (N = 98) and healthy comparison subjects (N = 50). The patients were assessed by means of semi-structured interviews and diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…Neuropsychological studies of Leonhard's subtypes are scarce and mainly address only some of the subtypes. Our results are in agreement with a previous cross-sectional study of our group (Cuesta et al, 2022) that found that premorbid cognitive achievement was significantly lower in SSch compared with the other three groups. In general, SSch showed the greatest cognitive impairment, USch showed an intermediate performance, and Cyclo and MDI were the least impaired in cognitive domains.…”
Section: Discussionsupporting
confidence: 93%
“…Neuropsychological studies of Leonhard's subtypes are scarce and mainly address only some of the subtypes. Our results are in agreement with a previous cross-sectional study of our group (Cuesta et al, 2022) that found that premorbid cognitive achievement was significantly lower in SSch compared with the other three groups. In general, SSch showed the greatest cognitive impairment, USch showed an intermediate performance, and Cyclo and MDI were the least impaired in cognitive domains.…”
Section: Discussionsupporting
confidence: 93%